К изучению морфологии днепровских рыб рода ельцовых (Leuciscus, Cyprinidae) и их таксономического сходства - Павлов, П.И.; Щербуха, А.Я. (Вестник зоологии, 1972)
The article deals with a description of meristic and plastic characters and data on growth of Leuciscus leuciscus (L.), L. borysthenicus (Kessl.), L. cephalus (L.) and L. idus (L.) from the Dnieper.
As a result of pair comparison of morphological characters of all four species by means of biometrical methods the number of characters is shown by which the species under consideration do not differ. The processing of these data by E. S. Smirnov's method of taxonomic analysis permitted the degree of morphological similarity of the Leuciscus species and degree of uniqueness in each of them to be shown and a conclusion on the Leuciscus genus structure to be made. At the same time it is shown that the conclusions. on the taxon structure of fish are scanty if they are based only on the data of fish morpho-logy.